Dehumanisation in religious and sectarian violence: the case of Islamic State. Issue 4 (1st October 2016) - Ramsay, Gilbert
ABSTRACT: It is often taken more or less for granted that perpetrators of mass killings and other acts of violent atrocity dehumanise their victims in order to justify killing them. Drawing on the past decade of developments in psychological theories of dehumanisation, and on representations and explanations of killing provided by Islamic State, this paper argues for a more complex understanding of the role of notions about humanity and inhumanity in the legitimation of violence.